Understanding attitudes and self-efficacy of in-service teachers and professionals towards inclusive education in the Republic of Armenia - Alaverdyan, Vahan (2018)
The concept and practices of inclusive education have been spreading worldwide for over two decades, pushing governments to adopt child-centered policies and consider basic school education as a fundamental human right for all children. This movement has created mixed attitudes and problematic perceptions among teachers who have to teach children in special needs education. Transitioning from a dual school system to an inclusive one is an ongoing process in the Republic of Armenia and the aim of the current study is to understand the Armenian teachers’ overall attitudes towards inclusive education and their self-efficacy for inclusive practices. А quantitative study was conducted to understand teachers’ attitudes and self-efficacy towards inclusive education. The data was collected from 187 in-service teachers from 11 mainstream schools. The respondents completed a questionnaire on their Sentiments, Attitudes, and Concerns about Inclusive Education Revised (SACIE-R) scale (Forlin, Earle, Loreman & Sharma, 2011) and the Teacher Efficacy for Inclusive Practices (TEIP) scale (Sharma, Loreman, and Forlin, 2011). The analysis revealed that the Armenian teachers’ attitude formation depends on different factors. For example, the higher the level of the inclusive education training was, the more positive were the attitudes. Also, the teachers’ sentiments towards direct contact with children with disabilities were higher than concerns and attitudes. The data also indicated that the teachers’ level of concerns with including learners with disabilities in their classes was mostly dependent on how they felt about implementing the inclusive practices.